Physicochemical Compatibility of Parenteral Medications Used in Neonatal Intensive Care - De Silva, Dadallage Thisuri Nayanthi (Curtin University, 2024)
Premature babies in neonatal intensive care units often require treatment with several intravenous medications. Physical and chemical compatibility is essential, to avoid adverse effects and ensure effective patient care. Published research from the past 50 years was reviewed, to prepare a comprehensive guide on compatible and incompatible drug combinations. The compatibility of sildenafil and caffeine, with over 40 other intravenous drugs, was investigated. This thesis provides valuable information to improve the care of vulnerable babies.